The cartoonist - Byars, Betsy Cromer; Cuffari, Richard 1925-. (New York Puffin Books, 1987)
Threatened with the loss of his private place in the attic of his crowded home, a young boy determines to keep it at all costs.
Keywords: Family life -- Fiction